PENERAPAN TAKSONOMI BLOOM DALAM KEMAMPUAN BERPIKIR MENYELESAIKAN SOAL GEOMETRI PADA SISWA KELAS VIII - Yohana Regnisia Afirda; Sofia Sa’o; Yasinta Yenita Dhiki (Program Studi Pendidikan Matematika, 2020)
This research was conducted at SMP Negeri 2 Ende in the 2018/2019 school year. The purpose of this study was to describe: the ability to think in solving geometry problems in class VIII students using Bloom's taxonomy in the cognitive domain, the ability to think in solving geometric problems in class VIII students using Bloom's taxonomy in the affective domain, the ability to think in solving geometric problems in class VIII students using Bloom's taxonomy. psychomotor realm. This type of research is a descriptive study using qualitative methods. Data collection techniques using written tests, interviews, observation, and documentation. The subjects in this study were six students who were selected based on 3 groups of ability, namely high, medium, and low. The selection of research subjects was based on written test results. The results showed that based on Bloom's taxonomy, the thinking abilities of class VIII A students of SMP Negeri 2 Ende in solving geometry problems were as follows: in the higher thinking group the ability to think was at the level of analysis. Students in the medium ability group are at the application level and students in the low ability group are at the knowledge level.